Analysis of the health status and its influencing factors of the low-income populations in Wuxi, China - Li, Shiming; Jiang, Ying; Wu, Yue; Ji, Yingying; Tian, Lin; Yang, Queping; Zhu, Haohao (Frontiers in Public Health, 2024)
Objective To understand the physical health condition and its influencing factors among the low-income population. Method Low-income residents who visited or consulted at our Hospital during 2022 were selected for this study. Through telephone or face-to-face interviews, a self-made basic information questionnaire was used for data collection. The physical health level of the low-income population was analyzed, and a logistic regression model was applied to study its influencing factors. Results A total of 2,307 people were included in this study, of which 2,069 had various types of diseases, indicating a disease rate of 89.68%. Multivariate logistic regression analysis showed that age ≥ 60 years old (OR = 1.567, 95%CI: 1.122–2.188), poor mental health status (OR = 2.450, 95%CI: 1.203–3.678), smoking (OR = 1.752, 95%CI: 1.269–2.206), pulse pressure difference ≥ 60 (OR = 1.485, 95%CI: 1.164–1.787), and poor hearing (OR = 1.268, 95%CI: 1.026–1.324) were risk factors for disease, whereas being female (OR = 0.729, 95%CI: 0.540–0.984) was a protective factor for physical health. Conclusion As a developing country with a large population, we should particularly focus on the physical health issues of the low-income population, take targeted measures for disease situations, and improve the quality of life of the low-income population.